Influence of irrigation on yield and quality of cv. Touriga Franca in the Douro Region - Cabral Inês; Nogueira Tiago; Carneiro Anabela; Queiroz Jorge (E3S Web of Conferences, 2018)
The Douro Region is characterized by a typically Mediterranean climate, with extreme temperatures and irregular rainfall throughout the year. This experimental trial was carried out on a vineyard plot of Touriga Franca, grafted in 110R, at Quinta da Cabreira, property of Quinta do Crasto, S.A., located in the Douro Region. Four irrigation modalities were established, in three blocks, according to the percentage of cultural evapotranspiration (ETc): R0, the control, without irrigation; R25, irrigated with 25% ETc; R50, with 50% ETc and R75, with 75% ETc. Irrigation had repercussions on total leaf area, with statistically significant lower value for R0 and greater for R75. Concerning the ecophysiological parameters, the water leaf potential was lower in R0 than at R50 and R75. On the yield components, it was observed a higher number of clusters in R75 and a smaller quantity in R0 and the bunch weight was also affected by the amount of water provided, with the R50 or R75 having a higher value. Even if the berry weight has not presented differences, those factors affect yield, that was higher in the R50 and R75. Concerning the quality, no significant differences had been found on the various components tested.